Criminal law principles in the fight against crime - Воробей, Петро Адамович; Воробей, П. А.; Воробей, Петр Адамович; Vorobei, Petro A.; Vorobey, Petro; Воробей, Олена Вячеславівна; Воробей, О. В.; Воробей, Елена Вячеславовна; Vorobei, Olena V.; Vorobey, Olena; Матвійчук, Валерій Костянтинович; Матвійчук, В. К.; et al. (Editorial Primmate S. A. S., 2022)
The purpose of the article is to analyze the criminal law principles in the fight against crime, to introduce a distinction between them and general principles of the State. The subject of the study is the criminal law principles in the fight against crime. Methodology. The following methods were used to achieve the goal of the Article: formal logic; description; historical and legal; comparative law; dogmatic. Results of the research. The paper analyzes and criticizes the criminal law principles in the fight against crime. Their essence and significance in the general context of combating crime are highlighted. Each principle is analyzed separately in the context of their relationship with the general principles of criminal law policy of the State. Practical meaning. It is proposed not to consider the principle of justice as criminal law one, but to place itwithin the framework of general philosophical principles and categories such as kindness, decency, humanism, humanity, honesty, etc. Value / originality. It is confirmed that the law on criminal liability must be fair, and therefore effective, which stemsfrom the very matter of justice as a socio-philosophical category.
Vorobey P. Criminal law principles in the fight against crime / P. Vorobey, O. Vorobey, V. Matviichuk, A. Niebytov, I. Khar // Amazonia Investiga. – Vol. 11. - Issue 49. – Editorial Primmate S. A. S., 2022. – P. 156-164.
Keywords: concepts; criminal law principles; interrelation; legal categories; philosophical categories; кримінально-правові принципи; філософські категорії; взаємозв'язок; правові категорії; поняття; Research Subject Categories::LAW/JURISPRUDENCE